2019
DOI: 10.3390/jcm8020164
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Analysis in Patients Going through a Depressive Episode during Treatment in a Psychiatric Hospital Setting

Abstract: Rationale: There is a worldwide prevalence of generalized anxiety and major depressive disorders (MDD). Gut–brain axis dysfunction, antibacterial activity, and modulatory effects of antidepressants toward intestinal bacteria have been shown both in vitro and in vivo. Objectives: In this study, we aimed to investigate the effects of hospital stay, including escitalopram administration, on gut microbiota in patients with depressive episodes. Methods: After admission to the hospital and 7-days washout from all me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…A previous animal study reported a significant difference in specific species composition between rats treated with escitalopram and those receiving vehicle, while the beta diversity in principal coordinate analysis did not differ significantly ( Cussotto et al, 2018 ). Moreover, a recent human study did not show a significant change regarding beta diversity after 6 weeks’ intake of escitalopram in a controlled hospital setting ( Liskiewicz et al, 2019 ). Our results were in line with these previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous animal study reported a significant difference in specific species composition between rats treated with escitalopram and those receiving vehicle, while the beta diversity in principal coordinate analysis did not differ significantly ( Cussotto et al, 2018 ). Moreover, a recent human study did not show a significant change regarding beta diversity after 6 weeks’ intake of escitalopram in a controlled hospital setting ( Liskiewicz et al, 2019 ). Our results were in line with these previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…One previous study by Liskiewicz et al (2019) focused longitudinally on the relationship between depression severity and gut microbial diversity among 17 patients in a hospital setting. A significant increase in alpha diversity in the Shannon index was observed after 6 weeks of pharmacotherapy, but not in the Chao1 index.…”
Section: Introductionmentioning
confidence: 99%
“…This latter species is known to have beneficial anti-inflammatory properties and can protect against gut barrier dysfunction and fat mass development 37 . More recently, an increase in fecal microbiota biodiversity, mainly alpha diversity was shown in human patients after six weeks of concomitant therapy using 5-20 mg of escitalopram 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The human intestine contains the largest community of the roughly 100 trillion (Sender et al, 2016) commensal and symbiotic bacteria (Marietta et al, 2015). It influences the immune system (Thaiss et al, 2016), autoimmunity (Shamriz et al, 2016), allergies (Prince et al, 2015), inflammatory bowel disease (Frank et al, 2011), depression (Liśkiewicz et al, 2019), the wellbeing (Neto & O'Toole, 2016) and the BMI (Chen et al, 2014), (Goodrich et al, 2014). The gut-associated lymphoid tissue (GALT) is our largest immunologic organ with over 70% of the total immune system.…”
Section: Introductionmentioning
confidence: 99%